Answer
3 MgO + 2 NH₃ → Mg₃N₂ + 3 H₂O
Step-by-step explanation
The given unbalanced equation is:
MgO +_NH₃ → Mg₃N₂ + __H₂O
Step 1: Balance the Mg atom by putting 3 as coefficient of MgO in the reactant side.
3 MgO +_NH₃ → Mg₃N₂ + __H₂O
Step 2: Balance the N atom on both sides by putting 2 as the coefficient of NH₃ in the reactant side.
3 MgO + 2 NH₃ → Mg₃N₂ + __H₂O
Step 3: Balance the H and O atoms on both sides by putting 3 as the coefficient of H₂O in the product side.
3 MgO + 2 NH₃ → Mg₃N₂ + 3 H₂O
Hence, the equation is balanced: 3 MgO + 2 NH₃ → Mg₃N₂ + 3 H₂O